Effects of a novel chitosan based macromolecule antioxidant COS-GMMP on the thermo-oxidative aging of styrene-butadiene rubber/silica composites. (January 2022) - Ding, Pan; Zou, Yongkun; He, Jingwei; Sun, Yangkun; Liu, Fang
Highlights: A novel chitosan based macromolecule hindered phenol antioxidant (COS-GMMP) was synthesized via Michael addition reaction and acylation reaction. The chemical structure of COS-GMMP was characterized and confirmed by 1H-NMR, 13C-NMR, FTIR and elemental analysis. COS-GMMP significantly improved the thermo-oxidative aging resistance, thermal-oxidative stability and hot-water extraction resistance of SBR/silica composites more effectively than the low molecule hindered phenol antioxidant GM. Abstract: A chitosan based macromolecule antioxidant (COS-GMMP) was prepared by using chitosan (COS), 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylphenyl) methyl-4-methylp-henyl acrylate (antioxidant GM) and 3-mercaptopropionic acid (MPA) via Michael addition reaction and acylation reaction. The chemical structure of COS-GMMP was confirmed by 1 H NMR, 13 C NMR, FTIR and elemental analysis. The anti-aging behavior of styrene-butadiene rubber (SBR)/silica with COS-GMMP, as well as the low molecule antioxidant GM, was systematically investigated by the accelerated thermal aging tests, oxidation induction time (OIT), thermo-gravimetric analysis (TGA) and hot water extraction experiments. The results revealed that COS-GMMP significantly improved the thermo-oxidative aging resistance, thermal-oxidative stability and solvent extraction resistance of SBR/silica composites more effectively than the antioxidant GM. The preeminent antioxidative ability of COS-GMMP for SBR/silica composites was attributed to not only the synergistic antioxidative effect among hindered phenol, amide and thioether groups, but also its high molecular weight.